Peran Guru dalam Pembelajaran Membaca dan Menulis Siswa SD Kelas Rendah - Khair, Ummul; Kholik, Kholik (ESTETIK : Jurnal Bahasa Indonesia, 2023)
This research was carried out at SDN 06 Rejang Lebong in the second semester. The problem identified in this research was the lack of reading and writing skills among lower class students. Aims to describe reading errors and writing difficulties in lower grade students and describe the role of teachers in improving reading and writing skills in elementary school students. Using a qualitative approach with the type of research being descriptive. The subjects of this research were the school principal, teacher council, and lower grade teacher. Data collection by observation, interviews and documentation. Data analysis uses three stages consisting of data reduction, data presentation, and drawing conclusions. Inspection or checking the validity of the data is carried out using technical triangulation and source triangulation. The results of the research show that the forms of reading errors in lower grade students are children's difficulty recognizing the letters of the alphabet, errors in reading each word, and errors in pronunciation of words and use of lip movements. Meanwhile, the forms of writing errors include errors in writing words or sentences and errors in writing numbers. The role of the teacher in improving the reading and writing skills of low grade students includes: (1) the teacher acts as a demonstrator in learning activities, (2) the teacher acts as a class manager, (3) the teacher acts as a learning mediator, (4) the teacher acts as a facilitator in learning (5) )teachers also act as motivators for students. Things that hinder teachers' efforts include student motivation, student interest in learning, students' seriousness in learning and teachers' learning methods that are still contextual, as well as things that support the teacher's role include adequate school facilities and support from the school principal in learning.